Brain microstructural development at near-term age in very-low-birth-weight preterm infants: An atlas-based diffusion imaging study - Rose, Jessica (2013)
At near-term age the brain undergoes rapid growth and development. Abnormalities identified during this period have been recognized as potential predictors of neurodevelopment in children born preterm. This study used diffusion tensor imaging (DTI) to examine white matter (WM) microstructure in very-low-birth-weight (VLBW) preterm infants to better understand regional WM developmental trajectories at near-term age. DTI scans were analyzed in a cross-sectional sample of 45 VLBW preterm infants (BW ≤ 1500 g, GA ≤ 32 weeks) within a cohort of 102 neonates admitted to the NICU and recruited to participate prior to standard-of-care MRI, from 2010 to 2011, 66/102 also had DTI. For inclusion in this analysis, 45 infants had DTI, no evidence of brain abnormality on MRI, and were scanned at PMA ≤40 weeks (34.7–38.6). White matter microstructure was analyzed in 19 subcortical regions defined by DiffeoMap neonatal brain atlas, using threshold values of trace b0.006 mm(2) s(−1) and FA >0.15. Regional fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were calculated and temporal–spatial trajectories of development were examined in relation to PMA and brain region location. Posterior regions within the corona radiata (CR), corpus callosum (CC), and internal capsule (IC) demonstrated significantly higher mean FA values compared to anterior regions. Posterior regions of the CR and IC demonstrated significantly lower RD values compared to anterior regions. Centrally located projection fibers demonstrated higher mean FA and lower RD values than peripheral regions including the posterior limb of the internal capsule (PLIC), cerebral peduncle, retrolenticular part of the IC, posterior thalamic radiation, and sagittal stratum. Centrally located association fibers of the external capsule had higher FA and lower RD than the more peripherally-located superior longitudinal fasciculus (SLF). A significant relationship between PMA-at-scan and FA, MD, and RD was demonstrated by a majority of regions, the strongest correlations were observed in the anterior limb of the internal capsule, a region undergoing early stages of myelination at near-term age, in which FA increased (r = .433, p = .003) and MD (r = –.545, p = .000) and RD (r = –.540, p = .000) decreased with PMA-at-scan. No correlation with PMA-at-scan was observed in the CC or SLF, regions that myelinate later in infancy. Regional patterns of higher FA and lower RD were observed at this near-term age, suggestive of more advanced microstructural development in posterior compared to anterior regions within the CR, CC, and IC and in central compared to peripheral WM structures. Evidence of region-specific rates of microstructural development was observed. Temporal–spatial patterns of WM microstructure development at near-term age have important implications for interpretation of near-term DTI and for identification of aberrations in typical developmental trajectories that may signal future impairment.